2010
DOI: 10.1123/jpah.7.5.577
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Marriage and Parenthood on Physical Activity: A 2-Year Prospective Analysis

Abstract: Background-Physical activity (PA) tends to decrease from adolescence to young adulthood, and factors that have been proposed to contribute to this decrease are life transitions. The focus of this study is to examine life transitions, such as marriage and parenthood, and the impact they may have on the physical activity levels of young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
151
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(167 citation statements)
references
References 35 publications
(57 reference statements)
12
151
2
2
Order By: Relevance
“…A similar argument was given by Burton and Turrell (2000), who concluded that in general, the physical activity of men and women is different and that parenthood may have a greater effect on physical activity in mothers than on fathers. Interestingly, other studies have shown a reduction in physical activity in mothers, especially in mothers of young children (Candelaria et al 2012;Hull et al 2010). These contradictory results may have been related to differences in the definition of physical activity (as opposed to sporting activity) and the methods used to measure physical activity.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A similar argument was given by Burton and Turrell (2000), who concluded that in general, the physical activity of men and women is different and that parenthood may have a greater effect on physical activity in mothers than on fathers. Interestingly, other studies have shown a reduction in physical activity in mothers, especially in mothers of young children (Candelaria et al 2012;Hull et al 2010). These contradictory results may have been related to differences in the definition of physical activity (as opposed to sporting activity) and the methods used to measure physical activity.…”
Section: Discussionmentioning
confidence: 92%
“…Social control in particular seems to be an important determinant of health behaviour, affecting health behaviours directly (e.g., sanctions for deviant behaviour, regulation, and physical intervention) and indirectly (e.g., internalisation of norms of healthful behaviour and facilitation of positive health behaviours) (Umberson 1987). There may also be mechanisms by which having a partner and living with children could lead to a decrease in healthy behaviour (e.g., stress caused by combined social roles, social and domestic responsibilities, increased demands on time, or discord in the relationship) (Brown et al 2009;Eng et al 2005;Hull et al 2010;Nomaguchi and Bianchi 2004). A transition to divorce or widowhood could also be detrimental to health because of the loss of social control or social support provided by a partner.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…There have been significant findings relating age-specific life transitions to changes in PA levels [3,4,5]. When focusing on PA changes in women, it has been observed that PA levels decreased significantly after marriage and childbirth, and as women aged and their health declined [6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Hull et al (65) noted that physical activity tends to decrease as young adults age from 24 to 26 years old. Nevertheless, the marriage did not significantly change physical activity.…”
mentioning
confidence: 99%